PENGARUH CAPITAL ADEQUACY RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL , NON PERFORMING LOAN, NET INTEREST MARGIN DAN LOAN TO DEPOSIT RATIO TERHADAP RETRUN ON ASSET - Nilawati Nilawati; Ibnu Hajar; Wahuniati Hamid (Pascasarjana Universitas Halu Oleo, 2019)
This research intends to partially examine the effect of Capital Adequacy Ratio (CAR), Operational Costs Operational Income (BOPO), Non Performing Loans (NPL), Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) to Return on Assets (ROA) at Persero Bank. The subject of this research was persero banks consisting of Bank Mandiri, Bank Rakyat Indonesia, Bank Negara Indonesia and Bank Tabungan Negara with observation period of 15 years, thus the research data observed was 60 observations. The data were analyzed with multiple analysis using SPSS 20. The result of the research: 1) capital adequacy ratio has negative and insignificant effects on persero banks' Return on Assets, 2) operational costs operational income has negative and significant effects on persero banks' Return on Assets, 3) non-performing loans has negative and significant effects on persero banks' Return on Asset, 4) net interest margin has positive and significant effects on persero banks' Return on Assets, 5) loan to deposit ratio has positive but insignificant effects on persero banks' Return on Assets.Keywords: CAR, Operating Income Operating Costs, NPL, NIM, LDR, ROA